Combining interleukin 6 and EBV DNA levels predicts survival outcomes for patients with recurrent or metastatic nasopharyngeal carcinoma receiving chemoimmunotherapy - Liu, Ya; Huang, Zilu; Chen, Chen; Hu, Yujun; Tao, Yalan; Liu, Songran; Feng, Ping; Zheng, Shuohan; Xia, Yunfei (Frontiers in Immunology, 2025)
PurposePlatinum-based chemotherapy plus PD-1 inhibitors (chemoimmunotherapy) was the standard systemic treatment for recurrent or metastatic nasopharyngeal carcinoma (R/M NPC). However, biomarkers to predict the survival outcomes remained unsatisfying. This study aimed to establish a simple but easily applicable model to predict the survival outcomes of R/M NPC receiving chemoimmunotherapy.Materials and methodsA total of 319 R/M NPC patients treated by chemoimmunotherapy with or without local therapy at our hospital were randomly divided into training (n=223) and validation (n=96) cohorts at a ratio of 7:3. An easily applicable prognostic risk grouping model was created using common independent predictors of progression-free survival (PFS) and overall survival (OS) in the training set. Model performance was assessed in the validation set.ResultsPretreatment IL-6 and EBV DNA levels were identified as independent prognostic factors (scored on 0-4 points), and used to develop a prognostic risk grouping model with distinct survivals: 0-1 point (low risk), 2-3 points (intermediate risk), and 4 points (high risk). In the training set, the median PFS were not reached (NR), 18.90, and 7.73 months (P<0.001) respectively in the low-, intermediate-, and high-risk groups, while the median OS were NR, NR and 13.6 months (P<0.001). Results were further confirmed in the validation set.ConclusionThis model predicted both PFS and OS in R/M NPC patients undergoing chemoimmunotherapy. This finding may help clinicians with an initial prognostic estimation but warrants further prospective investigation for the value of IL-6 and EBV DNA.